Navigating Gender Sexism on Social Media: Challenges and Collective Solidarity Among Hijab-Wearing Women in Muslim Fashion Trends on TikTok - Isnawijayani, Isnawijayani; Widayatsih, Tri; Widhi, Diana; Lexianingrum, Siti Rahayu Pratami; Taqwa, Dwi Muhammad; Amelia, Fara (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to understand the experiences of women wearing the hijab in facing gender sexism on the TikTok platform, especially related to Muslim fashion trends. Through a digital ethnographic approach, this research analyzes the content, comments, and social interactions of ten active participants in the TikTok hijab fashion community who have experienced or witnessed negative comments. The research results show that the TikTok platform, with its algorithm that personalizes content, helps reinforce gender bias through repeated exposure to negative comments and stereotypes. These findings also reveal a complex dynamic in which criticism of modern hijab fashion often comes from fellow women, but it is necessary to examine further the social and cultural factors that underlie this phenomenon. This research highlights the importance of understanding how social media platforms can shape the perceptions and experiences of women wearing the hijab and calls for efforts to build more inclusive and supportive online communities.